2001
DOI: 10.1038/nm1101-1202
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of matrix metalloproteinases blocks lethal hepatitis and apoptosis induced by tumor necrosis factor and allows safe antitumor therapy

Abstract: Acute and fulminant liver failure induced by viral hepatitis, alcohol or other hepatotoxic drugs, are associated with tumor necrosis factor (TNF) production. In a mouse model of lethal hepatitis induced by TNF, apoptosis and necrosis of hepatocytes, but also lethality, hypothermia and influx of leukocytes into the liver, are prevented by a broad-spectrum matrix metalloproteinase (MMP) inhibitor, BB-94. Mice deficient in MMP-2, MMP-3 or MMP-9 had lower levels of apoptosis and necrosis of hepatocytes, and better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
146
2
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(161 citation statements)
references
References 44 publications
11
146
2
2
Order By: Relevance
“…Gelatin zymography was performed with extracted proteins from the liver (50 g) as previously described. 9 Quantitative Real-Time Reverse-Transcriptase Polymerase Chain Reaction. Extracted RNA from the liver and the isolated cells was reverse-transcribed, and quantitative real-time polymerase chain reaction with probe-primers sets of SphK1, TIMP-1, and 18S ribosomal RNA (Applied Biosystems, Foster City, CA) was performed using Taqman analysis (ABI Prism 7000 Sequence Detection System, Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin zymography was performed with extracted proteins from the liver (50 g) as previously described. 9 Quantitative Real-Time Reverse-Transcriptase Polymerase Chain Reaction. Extracted RNA from the liver and the isolated cells was reverse-transcribed, and quantitative real-time polymerase chain reaction with probe-primers sets of SphK1, TIMP-1, and 18S ribosomal RNA (Applied Biosystems, Foster City, CA) was performed using Taqman analysis (ABI Prism 7000 Sequence Detection System, Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…9 Although pro-and antiapoptotic mechanisms of apoptosis have been demonstrated, mechanisms of liver hemorrhage are not well understood.…”
mentioning
confidence: 99%
“…Consistent with this in vitro activity, TIMP3 blocks the release of TNF from cells in tissue culture 12 . TNF is a key inflammatory mediator that causes severe liver damage by a variety of mechanisms 13 (Fig. 1).…”
Section: Roy a Blackmentioning
confidence: 99%
“…Unfortunately, TNF also possesses strong proinflammatory properties, and its use is often accompanied by unacceptable shock symptoms, such as hypotension and organ failure (2)(3)(4). Initial studies in patients showed that the maximum tolerated dose (MTD) that can be applied systemically in humans is too low for effective tumor therapy (5).…”
Section: Introductionmentioning
confidence: 99%